DETECTION OF INFECTION ANAPLASMA SP., BORRELIA BURGDORFERI AND EHRLICHIA SP. IN THE DOG INFESTED WITH TICKS IN DENPASAR CITY - Perayadhista, Ni Made Devityasih; Suratma, Nyoman Adi; Dharmawan, Nyoman Sadra (Buletin Veteriner Udayana; Vol. 14 No. 5 October 2022DO - 10.24843/bulvet.2022.v14.i05.p16, 2022)
This research has been conducted as its purpose is to detect the infection of Anaplasma sp. , Borrelia burgdorferi , and Ehrlichia sp. in dogs as well as it was manifested with ticks in Denpasar City. The detection of these parasites was conducted by serological examination, haematology test, and microscopic identification with blood smear. Blood samples were examined from 30 dogs which is belong to local society and it also invested with Rhipichepalus sanguineus . Serological examination was performed with SNAP ® 4DX ® Plus test kit. Haematology examination were using haematology analyzer I-CUBIO iCell-800 Vet ® . The risk factor was learned by analyzing it with correlation to parasite infection case in dogs with a few factors which is considered being influenced. The result of serological examination shows that 22 of 30 dogs (73.3%) were positively reacted to Anaplasma sp. and Ehrlichia sp. but shown negative to Borrelia burgdorferi . In addition, haematology profile shown anemia, leucocytosis, leucopenia, lymphocitosis, lymphopenia, and thrombocytopenia, as well as abnormalities in blood cell morphology such as: poikilocytosis, and the presence of crenation. There is no correlation between blood pathogenic agents in this research to: age, breed, sex, origin, presence of other pets, or grooming management.